Ganglios Basales y Conducta. - Ospina-García, Natalia; Pérez-Lohman, Christian; Vargas-Jaramillo, Juan Diego; Cervantes-Arriaga, Amin; Rodríguez-Violante, Mayela (Revista Mexicana de Neurociencia)
Historically, the function of the basal ganglia has been a subject of debate and study. Initially it was proposed that these structures participated exclusively on the motor behavior; however, the current body of knowledge and science progress, allows to understand that these structures, and their connections, are determinant not only on motor behavior, but also in cognition and emotions. The present review describes the neuroanatomic and functional basis of the basal ganglia, emphasizing both the traditional schemes and the most recent models including sensorimotor, associative and limbic circuits, along with the relevance of reward systems.